Prior Drug-Related Criminal Charges and Risk for Intimate Partner Violence Perpetration Among Authorized Purchasers of Handguns in California - Pallin, Rocco (Journal of interpersonal violence, 2022)
Intimate partner violence (IPV) is a considerable public health problem in the US, and evidence suggests that both drugs and firearms contribute to the risk of IPV and its severity. This study uses a retrospective, longitudinal cohort design to explore the association between past arrests, charges incurred in the legal process, and convictions for drug-related crimes, and risk of future arrest for IPV among legal handgun purchasers. The cohort included all legal purchasers of handguns in California in 2001 between the ages of 21 and 49 (n = 79,678), 156 of whom had pre-purchase drug charges and post-purchase IPV charges. We used Cox proportional hazards regression with age at time of handgun purchase, sex, and race/ethnicity, and an array of community characteristics as covariates. Over the study period (2001-2013), in comparison to handgun purchasers who had no charges or convictions prior to their index purchase, risk for future IPV arrest was increased for purchasers whose only prior charges were drug-related (aHR = 3.4 [95% CI: 2.4-4.9]) and purchasers who had both prior drug- and non-drug related charges (aHR = 4.9 [95% CI: 4.1-6.0]). The magnitude of the risk ratio was greater when multiple drug types were involved and when the person had been charged with both the use and sale of drugs. Our findings suggest that, among legal handgun purchasers, prior drug charges are associated with future risk of IPV arrests or convictions. Given the established link between firearm access and IPV severity and fatality, these findings may inform the development and enforcement of policies that reduce firearm access for those at elevated risk of perpetrating intimate partner violence.